Regenerative Operation of 18/12 In-Wheel Switched Reluctance Motor for Electric Vehicle - Kaya, Ufuk; Oksuztepe, Eyyup (Ieee, 2019)
In this study, the regenerative operation of a in-wheel switched reluctance motor (IW-SRM) which is designed for electric vehicles (EV) is modeled. The electrical model of IW-SRM is created by using flux and moment values according to the current obtained from FEM analysis. Then, a regenerative study of IW-SRM was performed. Thus, the energy obtained from a downhill or braking EV is transferred to the battery and the vehicle range is increased. The reference current is adjusted to control the braking torque in regenerative operation of low speed direct driven IW-SRM. The validity of the model including the regenerative study of the IW-SRM is proved using Matlab/Simulink.
3rd International Conference on Applied Automation and Industrial Diagnostics (ICAAID) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: In-wheel SRM; Electric Vehicle; Regenerative Operation; FEM